Measurement invariance and latent mean differences of the Chinese version physical activity self-efficacy scale across gender and education levels - Han Chen; Jun Dai; Yong Gao (Elsevier, 2019)
Background: Self-efficacy has been identified as an important determinant of youth's behavior change including physical activity (PA) participation. However, the dimensionality check of a PA self-efficacy scale has rarely been conducted in China. The current study aims to examine (1) the unidimensionality of a shortened Chinese version of PA self-efficacy scale (S-PASESC); (2) the measurement invariance of S-PASESC across gender and levels of education; (3) the latent factor mean difference between gender and levels of education; (4) the direct effects of self-efficacy on PA by different gender and education levels; and (5) the comparisons of the direct effects of self-efficacy on PA across gender and education levels. Methods: The participants were 5th through 11th grade public school students recruited from 7 cities located in different geographic regions of China. The final data include a total of 3003 participants (49.7% boys) who have completed the scales. Results: Confirmatory factor analysis (CFA) test supported the unidimensionality of S-PASESC. The S-PASESC is invariant across gender and 3 levels of education at both configural, full metric, and full scalar levels. Findings from latent mean comparisons showed that boys reported higher PA self-efficacy than girls. Students' perceived PA self-efficacy tend to decrease from elementary to high school. Finally, self-efficacy positively related to PA by groups of different gender and education levels and the relationship between self-efficacy and PA is stronger among middle school boys than girls. Conclusion: Findings suggest S-PASESC is a valid scale for measuring Chinese students' PA self-efficacy. Keywords: Chinese adolescents, Education levels, Factor analysis, Gender, Latent mean comparison, Measurement invariance, Physical activity self-efficacy scale